(untitled) (Journal of Pharma Insights and Research, 2025)
Chalcones are a unique class of organic compounds characterized by their 1,3-diphenyl-2-propen-1-one structure, which serves as a crucial pharmacophore in medicinal chemistry. The inherent flexibility of the chalcone structure enables diverse biological activities, making them valuable leads in drug development. Recent advances in chalcone-based therapeutic agents demonstrate their potential in treating various pathological conditions, including cancer, inflammation, microbial infections, and neurodegenerative disorders. The α,β-unsaturated carbonyl system of chalcones facilitates multiple interaction patterns with biological targets, contributing to their broad spectrum of pharmacological effects. Molecular modification strategies applied to the basic chalcone scaffold have yielded numerous derivatives with enhanced potency and improved therapeutic profiles. The incorporation of heterocyclic moieties and various substituents on both aromatic rings has led to the development of novel drug candidates with optimized pharmacokinetic properties. Modern synthetic approaches, structure-activity relationships, and molecular mechanisms underlying the therapeutic effects of chalcones continue to expand their applications in pharmaceutical research. The advent of hybrid molecules incorporating chalcone pharmacophores presents promising directions for developing more effective therapeutic agents